Small-particle-size spherical green nitride fluorescent powder applied to MiniLED backlight source and preparation method of small-particle-size spherical green nitride fluorescent powder
By adopting the small-particle spherical green nitride phosphor with the chemical formula of Sr1-xEuxLiSi3N5, the problem of excessive particle size of the phosphor in the Mini LED backlight is solved, and the uniformity and efficiency of luminescence performance are achieved, meeting the high contrast and high color gamut requirements of Mini LED devices.
Patent Information
- Application Number
- CN202411982384.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In Mini LED backlights, the median particle size of traditional phosphors is too large, resulting in uneven luminous performance, which cannot meet the high contrast and high color gamut requirements of Mini LED devices.
A small-particle spherical green nitride phosphor with the general formula of Sr1-xEuxLiSi3N5 was used to form a SiO2 oxide layer through a high-temperature oxidation process, and combined with a pickling etching and washing process, the particle size was reduced to a median particle size of 0.5 μm to 1 μm.
In Mini LED backlight application, the appearance of the phosphor particles is spherical, the main peak of the emission spectrum is between 510 nm and 530 nm, and the quantum efficiency is between 40% and 60%, meeting the packaging needs of Mini LED backlight.
Smart Images

Figure CN119736087A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of fluorescent materials, and in particular to a small-diameter spherical green nitride phosphor for MiniLED backlight source application and a preparation method thereof. Background Art
[0002] At present, the mainstream display technology solutions include active light emission and backlight display technology. Representative solutions of active display technology include OLED, but the brightness of OLED is low. At the same time, because the luminous components of OLED are organic, the aging resistance is poor, so the service life of OLED is short. Micro LED is also one of the representative solutions of active display technology, but the mass transfer technology required to manufacture Micro LED is complicated and the yield rate is too low, resulting in high cost of Micro LED.
[0003] In the backlight display technology, Mini LED, which was launched in recent years based on the traditional LED backlight technology, has gradually become a hot spot in the display industry because of its advantages such as high color gamut, ultra-high contrast, and energy saving. The core of backlight technology is how to obtain white light. For Mini LED backlight sources, there are two solutions to achieve white light: Mini LED + quantum dot (film) solution and Mini LED + phosphor (film). The biggest obstacle faced by the application of quantum dots in Mini LED is the poor stability of quantum dots, which means that Mini LED devices based on quantum dots have a short service life, are not durable, and have low reliability.
[0004] In the Mini LED + phosphor (film) solution, the biggest problem is that the median particle size of the phosphor is too large. As we all know, phosphors are composed of individual fluorescent particles. Since most phosphors are obtained by high-temperature solid-phase reaction, the median particle size of these particles is usually about ten microns; in addition, the high-temperature solid-phase reaction occurs in a heterogeneous system. Therefore, the luminescence performance of the fluorescent particles obtained under high-temperature solid-phase reaction conditions cannot be exactly the same, and there are fluctuations and differences in quantum efficiency and luminescence intensity between particles. In the traditional LED backlight technology solution, since the (planar) size of the chip used is millimeter-level, when the phosphor with a median particle size of more than ten microns is coated on the millimeter-level chip, the fluctuations in the luminescence performance of individual phosphor particles (in a statistical sense) will not lead to obvious differences in the luminescence performance of the final packaged device. However, when the technology develops to Mini LED, since the plane size of Mini LED is only tens to hundreds of microns, if the traditional phosphor with a median particle size of more than ten microns is still used at this time, the luminescence performance of the packaged MiniLED will not be uniform. This is because the planar size of Mini LED is only tens to hundreds of microns, while the median particle size of phosphor is more than ten microns, which means that there are only dozens to hundreds of phosphor particles coated on a Mini LED chip. The fluctuations in the luminescence performance of individual phosphor particles (in a statistical sense) will completely lead to obvious differences in the luminescence performance of the final packaged devices.
[0005] The most direct way to eliminate the problem of obvious differences in the luminous performance of the final packaged device caused by the fluctuations (in a statistical sense) in the luminous performance of individual phosphor particles is to reduce the median particle size (value) of the phosphor. The simplest way to reduce the median particle size is to use ball milling to grind the obtained phosphor. Due to the high hardness of phosphor particles, long-term ball milling greatly damages the surface morphology of the particles. Although ball milling reduces the particle size of the phosphor, it also brings a negative effect, that is, it significantly reduces the luminous intensity of the phosphor. That is, ball milling is not the best way to obtain small-particle phosphors for MiniLED backlight applications. Summary of the invention
[0006] The purpose of the present invention is to solve the above-mentioned problems in the prior art and to provide a small-particle spherical green nitride phosphor for MiniLED backlight source application and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme:
[0008] A small-particle spherical green nitride phosphor for MiniLED backlight application, wherein the small-particle spherical green nitride phosphor is made of Sr 1-x Eux The general chemical formula of LiSi3N5 is represented, wherein 0.01≤x≤0.07; the main peak of the emission spectrum of the small-particle spherical green nitride phosphor under 450 nm blue light excitation is 510 nm to 530 nm; the D50 median particle size of the small-particle spherical green nitride phosphor is 0.5 μm to 1 μm.
[0009] The small-particle spherical green nitride phosphor can absorb violet light and blue light; under the excitation of 450 nm blue light, the quantum efficiency of the small-particle spherical green nitride phosphor is 40% to 60%.
[0010] The method for preparing a small-diameter spherical green nitride phosphor for MiniLED backlight source application comprises the following steps:
[0011] 1) Sr3N2, EuN, Li3N and Si3N4 are mixed evenly under a protective atmosphere, and then sintered under an ammonia atmosphere to obtain a first powder;
[0012] 2) grinding the first powder and heat treating it in an oxidizing atmosphere to obtain a second powder;
[0013] 3) mixing the second powder with HF acid, heating and stirring to obtain a mixture;
[0014] 4) filtering the mixture in step 3) using a filter membrane, and drying the obtained solid to obtain a third powder;
[0015] 5) Repeating step 2), step 3) and step 4) for 4 times on the third powder to obtain a fourth powder;
[0016] 6) washing the fourth powder with deionized water to obtain a fifth powder;
[0017] 7) Drying the fifth powder to obtain the small-size spherical green nitride phosphor.
[0018] In step 1), the molar ratio of Sr to Eu to Li to Si in the Sr3N2, EuN, Li3N and Si3N4 is (1-x):x:1:3.
[0019] In step 1), the pressure of the ammonia atmosphere is 1.5 MPa to 2 MPa, the sintering temperature is 1550° C. to 1600° C., and the sintering time is 6 h to 10 h.
[0020] In step 2), the heat treatment temperature is 1000° C. to 1100° C., and the heat treatment time is 25 min to 30 min.
[0021] In step 6), washing is performed until no fluoride ions are detected.
[0022] A Mini LED backlight source comprises: a Mini LED and a wavelength conversion material, wherein the wavelength conversion material comprises a small-particle spherical green nitride phosphor or.
[0023] The emission wavelength range of the Mini LED is 380 nm to 480 nm, and the plane size is 200 μm×200 μm.
[0024] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0025] The present invention provides a small-particle spherical green nitride phosphor for MiniLED backlight source application and a preparation method thereof. The small-particle spherical green nitride phosphor can be Sr 1-x Eu x The general chemical formula of LiSi3N5 is represented by 0.01≤x≤0.07. The present invention intentionally uses a high-temperature oxidation process to oxidize the nitride phosphor so that a SiO2 oxide layer is formed on the surface of the particles, and combines acid etching, washing and other processes to eliminate the SiO2 oxide layer, and finally obtains a spherical shape of the phosphor particles, a D50 median particle size of 0.5 μm to 1 μm, a quantum efficiency of 40% to 60% under 450 nm blue light excitation, and a main peak of the emission spectrum of 510 nm to 530 nm, and a small-diameter spherical green nitride phosphor for MiniLED backlight applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the emission spectrum of the material obtained in Comparative Example 1 under 450 nm blue light excitation;
[0027] Figure 2 This is the emission spectrum of the material obtained in Comparative Example 1 under 450 nm blue light excitation;
[0028] Figure 3 This is the emission spectrum of the material obtained in Example 5 under 450 nm blue light excitation;
[0029] Figure 4 This is a physical picture of the device obtained in Example 8. DETAILED DESCRIPTION
[0030] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0031] The present invention provides a small-particle spherical green nitride phosphor for MiniLED backlight source application. The chemical formula of the small-particle spherical green nitride phosphor can be Sr 1-x Eu xLiSi3N5 represents, wherein 0.01≤x≤0.07; the small-particle spherical green nitride phosphor can absorb purple light and blue light; under 450 nm blue light excitation, the main peak of the emission spectrum of the small-particle spherical green nitride phosphor is between 510 nm and 530 nm; the small-particle spherical green nitride phosphor is composed of powdered particles, and the shape of the particles is spherical; the D50 median particle size of the small-particle spherical green nitride phosphor is 0.5 μm to 1 μm; under 450 nm blue light excitation, the quantum efficiency of the small-particle spherical green nitride phosphor is between 40% and 60%.
[0032] The small-size spherical green nitride phosphor is prepared by the following steps:
[0033] Step (A): Sr3N2, EuN, Li3N and Si3N4 are mixed uniformly in proportion under a protective atmosphere to obtain a mixed powder, and then the mixed powder is placed in a crucible and sintered under an ammonia atmosphere at a certain pressure to obtain a first powder;
[0034] Step (B): grinding the first powder obtained in step (A), placing it in a crucible, and heat treating it in an oxidizing atmosphere to obtain a second powder;
[0035] Step (C): mixing the second powder obtained in step (B) with HF acid, and then heating and stirring for 30 minutes to obtain a mixture;
[0036] Step (D): filtering the mixture obtained in step (C) through a filter membrane, and drying the solid matter on the filter membrane after filtration to obtain a third powder;
[0037] Step (E): the third powder obtained in step (D) is treated four times in sequence according to step (B), step (C), and step (D) to obtain a fourth powder;
[0038] Step (F): washing the fourth powder obtained in step (E) with deionized water to obtain a fifth powder;
[0039] Step (G): Dry the fifth powder obtained in step (F) to finally obtain a MiniLED backlight source having a chemical formula of Sr 1-x Eu x Small particle size spherical green nitride phosphor of LiSi3N5 (where 0.01≤x≤0.07).
[0040] In the above step (A), the purity of Sr3N2, EuN, Li3N and Si3N4 is not less than 99.5%; the molar ratio of Sr, Eu, Li and Si in Sr3N2, EuN, Li3N and Si3N4 is (1-x):x:1:3.
[0041] In the above step (A), the protective atmosphere used in the mixing process is nitrogen, and the pressure of the ammonia atmosphere during sintering is 1.5 MPa to 2 MPa. In an embodiment of the present invention, the pressure is preferably 2 MPa; the sintering temperature is 1550°C to 1600°C. In an embodiment of the present invention, the sintering temperature is preferably 1600°C; the sintering time is 6h to 10h. In an embodiment of the present invention, the sintering time is preferably 6h. The mixing process can be carried out in an environment familiar to those skilled in the art without any special restrictions. In the present invention, a glove box is preferably used. The sintering process can be carried out in an environment familiar to those skilled in the art without any special restrictions. In the present invention, a high-temperature furnace is preferably used. After the above sintering reaction is carried out, the first powder can be obtained by cooling the furnace to room temperature.
[0042] In the above step (B), the oxidizing atmosphere is an oxygen-nitrogen mixture with a volume ratio of 1:9, the heat treatment temperature is 1000°C to 1100°C, and in an embodiment of the present invention, the heat treatment temperature is preferably 1000°C; the heat treatment time is 25 minutes to 30 minutes, and in an embodiment of the present invention, the heat treatment time is preferably 30 minutes.
[0043] In the above step (C), the concentration of HF is 1 mol / L, and the mass ratio of the second powder to HF acid is 1:5; the heating temperature of the mixed solution is 60° C., and the stirring method is mechanical stirring.
[0044] In the above step (D), the filter membrane is made of polytetrafluoroethylene and has a pore size of 200 nm; the drying temperature is 100° C. and the drying time is 1 h.
[0045] In the above step (E), the third powder is processed 4 times according to the process sequence of step (B) → step (C) → step (D), and finally a fourth powder is obtained;
[0046] In the above step (F), the fourth powder is repeatedly washed with ionized water until fluoride ions are no longer detected in the washing wastewater, thereby finally obtaining the fifth powder.
[0047] In the above step (G), the drying temperature is 100° C. and the drying time is 1 h.
[0048] In some embodiments of the present invention, x is preferably 0.01; in some embodiments of the present invention, x is preferably 0.02; in some embodiments of the present invention, x is preferably 0.03; in some embodiments of the present invention, x is preferably 0.04; in some embodiments of the present invention, x is preferably 0.05; in some embodiments of the present invention, x is preferably 0.06; in other embodiments of the present invention, x is preferably 0.07.
[0049] After the reaction of steps (A) to (G) is carried out, a small-particle spherical green nitride phosphor for MiniLED backlight source application can be obtained.
[0050] The Mini LED backlight source is at least composed of Mini LED and a wavelength conversion material, and the wavelength conversion material at least includes Sr 1-x Eu x The small-particle spherical green nitride phosphor represented by the general chemical formula LiSi3N5 (wherein 0.01≤x≤0.07) and synthesized using the above preparation steps has an emission wavelength range of 380nm to 480nm and a plane size of 200μm×200μm for Mini LED.
[0051] Comparative Example 1
[0052] Follow the steps below to make it:
[0053] Sr3N2, EuN, Li3N and Si3N4 were mixed uniformly in a ratio of 0.95:0.05:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder. The mixed powder was then placed in a crucible and sintered at 1600°C in an ammonia atmosphere of 2 MPa for 6 hours.
[0054] The luminescence performance of the sample obtained in Comparative Example 1 was tested using a fluorescence spectrometer. The results are as follows: Figure 1 As shown. The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Comparative Example 1 is located at 522 nm. The median particle size of the obtained sample was measured using a laser particle size analyzer. The results showed that the D50 median particle size of the obtained sample was 14.9 μm. Obviously, this median particle size value is difficult to meet the packaging application for Mini LED backlight sources. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since the destructive ball milling process was not used, the result was 60.2% under 450 nm blue light excitation, which is a relatively high quantum efficiency value. See Table 1 for specific data.
[0055] That is, the material obtained in Comparative Example 1 is a green nitride phosphor, but since the D50 median particle size is too large, it cannot be applied to the packaging of Mini LED backlight sources.
[0056] Comparative Example 2
[0057] Follow the steps below to make it:
[0058] Step (A), Sr3N2, EuN, Li3N and Si3N4 are mixed in a ratio of 0.95:0.05:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder, and then the mixed powder is placed in a crucible, and sintered at 1600° C. in an ammonia atmosphere of 2 MPa for 6 hours to obtain a first powder;
[0059] Step (B), mixing the first powder obtained in step (A) with HF acid having a concentration of 1 mol / L in a mass ratio of 1:5, and mechanically stirring at 60° C. for 30 minutes to obtain a mixture;
[0060] Step (C), filtering the mixture obtained in step (B) through a polytetrafluoroethylene filter membrane with a pore size of 200 nm, and drying the solid matter on the filter membrane at 100° C. for 1 h to obtain a second powder;
[0061] Step (D), washing the second powder obtained in step (C) with deionized water until fluoride ions are no longer detected in the washing wastewater, to obtain a third powder;
[0062] Step (E), drying the third powder obtained in step (D) at 100° C. for 1 hour.
[0063] The luminescence performance of the sample obtained in Comparative Example 2 was tested using a fluorescence spectrometer. The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Comparative Example 2 is located at 521 nm. The median particle size of the obtained sample was measured using a laser particle size analyzer, and the results showed that the D50 median particle size of the obtained sample was 13.2 μm. Obviously, this median particle size value is difficult to meet the packaging application for Mini LED backlight sources. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since the destructive ball milling process was not used, the result was 59.9% under 450 nm blue light excitation, which is a high quantum efficiency value. That is, directly using HF acid to treat the sample obtained in Comparative Example 2 will not have a significant effect on the luminescence performance and median particle size of the obtained material. See Table 1 for specific data.
[0064] That is, the material obtained in Comparative Example 2 is a green nitride phosphor, but since the D50 median particle size is too large, it cannot be applied to the packaging of Mini LED backlight sources.
[0065] Comparative Example 3
[0066] Follow the steps below to make it:
[0067] Step (A), Sr3N2, EuN, Li3N and Si3N4 are mixed in a ratio of 0.95:0.05:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder, and then the mixed powder is placed in a crucible, and sintered at 1600° C. in an ammonia atmosphere of 2 MPa for 6 hours to obtain a first powder;
[0068] Step (B), grinding the first powder obtained in step (A) and placing it in a crucible, performing heat treatment in a 1:9 oxygen-nitrogen mixed atmosphere at a temperature of 1000° C. for 30 minutes, to obtain a second powder.
[0069] The luminescence performance of the sample obtained in Comparative Example 3 was tested using a fluorescence spectrometer. The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Comparative Example 3 is located at 510 nm. This is obviously because the heat treatment increases the oxygen content on the surface of the sample and oxidizes the Si in the material, which eventually leads to the formation of silicon dioxide on the surface of the particles, and then the emission spectrum of the sample has a certain blue shift due to the increase in oxygen content. The median particle size of the obtained sample was measured using a laser particle size analyzer. The results showed that the D50 median particle size of the obtained sample was 13.8 μm. Obviously, this median particle size value is difficult to meet the packaging application for Mini LED backlight sources. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since the destructive ball milling process was not used, the result was 12.7% under 450 nm blue light excitation, which is a low quantum efficiency value. Obviously, it is also because of oxidation that the silicon dioxide formed on the surface of the phosphor particles makes the sample white in color, the luminescence performance decreases, and the quantum efficiency is low. See Table 1 for specific data.
[0070] That is, the material obtained in Comparative Example 3 is a green nitride phosphor, but because the D50 median particle size is too large and the quantum efficiency is too low, it cannot be applied to the packaging of Mini LED backlight sources.
[0071] Comparative Example 4
[0072] Follow the steps below to make it:
[0073] Step (A), Sr3N2, EuN, Li3N and Si3N4 are mixed in a ratio of 0.95:0.05:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder, and then the mixed powder is placed in a crucible, and sintered at 1600° C. in an ammonia atmosphere of 2 MPa for 6 hours to obtain a first powder;
[0074] Step (B), grinding the first powder obtained in step (A) and placing it in a crucible, and heat treating it in a 1:9 oxygen-nitrogen mixed atmosphere at a temperature of 1000° C. for 30 minutes to obtain a second powder;
[0075] Step (C), mixing the second powder obtained in step (B) with HF acid having a concentration of 1 mol / L in a mass ratio of 1:5, and mechanically stirring at 60° C. for 30 minutes to obtain a mixture;
[0076] Step (D), filtering the mixture obtained in step (C) through a polytetrafluoroethylene filter membrane with a pore size of 200 nm, and drying the solid matter on the filter membrane at 100° C. for 1 h to obtain a third powder;
[0077] Step (E), washing the third powder obtained in step (D) with deionized water until fluoride ions are no longer detected in the washing wastewater, to obtain a fourth powder;
[0078] Step (F), drying the fourth powder obtained in step (E) at 100° C. for 1 hour, and finally obtaining a material.
[0079] The luminescence performance of the sample obtained in Comparative Example 4 was tested using a fluorescence spectrometer. The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Comparative Example 4 is located at 522 nm, which is similar to Comparative Example 1. The median particle size of the obtained sample was measured using a laser particle size analyzer. The results showed that the D50 median particle size of the obtained sample was 9.5 μm. Obviously, although this median particle size value is difficult to meet the packaging application for Mini LED backlight sources, this value is significantly lower than that of Comparative Example 1. This is obviously because silicon dioxide is generated on the surface of the particles (heat treatment under an oxidizing atmosphere), but after HF acid treatment, the silicon dioxide on the surface of the phosphor particles is corroded, resulting in a significant reduction in the final median particle size of the particles. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since no destructive ball milling process was used, the result was 58.9% under 450 nm blue light excitation. See Table 1 for specific data.
[0080] That is, the material obtained in Comparative Example 4 is a green nitride phosphor. Although its D50 median particle size has been significantly reduced, it still cannot be applied to the packaging of Mini LED backlight sources.
[0081] Example 1
[0082] Follow the steps below to make it:
[0083] Step (A), Sr3N2, EuN, Li3N and Si3N4 are mixed in a ratio of 0.99:0.01:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder, and then the mixed powder is placed in a crucible, and sintered at 1600° C. in an ammonia atmosphere of 2 MPa for 6 hours to obtain a first powder;
[0084] Step (B), grinding the first powder obtained in step (A) and placing it in a crucible, and heat treating it in a 1:9 oxygen-nitrogen mixed atmosphere at a temperature of 1000° C. for 30 minutes to obtain a second powder;
[0085] Step (C), mixing the second powder obtained in step (B) with HF acid having a concentration of 1 mol / L in a mass ratio of 1:5, and mechanically stirring at 60° C. for 30 minutes to obtain a mixture;
[0086] Step (D), filtering the mixture obtained in step (C) through a polytetrafluoroethylene filter membrane with a pore size of 200 nm, and drying the solid matter on the filter membrane at 100° C. for 1 h to obtain a third powder;
[0087] Step (E), the third powder obtained in step (D) is treated four times in sequence according to step (B), step (C) and step (D) to obtain a fourth powder;
[0088] Step (F), washing the fourth powder obtained in step (E) with deionized water until fluoride ions are no longer detected in the washing wastewater, to obtain a fifth powder;
[0089] Step (G), drying the fifth powder obtained in step (F) at 100° C. for 1 hour, and finally obtaining a material.
[0090] Using a scanning electron microscope, the appearance of the phosphor is approximately spherical. The luminescence performance of the sample obtained in Example 1 was tested using a fluorescence spectrometer. The test data is shown in Figure 2. The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Example 1 is located at 510 nm. The median particle size of the obtained sample was measured using a laser particle size analyzer. The results showed that the D50 median particle size of the obtained sample was 0.98 μm. Obviously, this median particle size value can meet the packaging application for Mini LED backlight sources. Compared with Comparative Example 1, this value has dropped significantly, which is obviously because silicon dioxide is generated on the surface of the particles (heat treatment under oxidizing atmosphere), but after HF acid treatment, the silicon dioxide on the surface of the phosphor particles is corroded, resulting in a significant decrease in the final median particle size of the particles; and compared with Comparative Example 4, after 5 oxidation / HF calculation washings, the median particle size of the phosphor particles can meet the requirements of the packaging application of Mini LED backlight sources. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since no destructive ball milling process was used, the result was 40.3% under 450 nm blue light excitation. See Table 1 for specific data.
[0091] That is, the material obtained in Example 1 is a green nitride phosphor and can meet the packaging requirements of Mini LED backlight sources.
[0092] Example 2
[0093] Follow the steps below to make it:
[0094] Step (A), Sr3N2, EuN, Li3N and Si3N4 are mixed in a ratio of 0.98:0.02:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder, and then the mixed powder is placed in a crucible, and sintered at 1600° C. in an ammonia atmosphere of 2 MPa for 6 hours to obtain a first powder;
[0095] Step (B), grinding the first powder obtained in step (A) and placing it in a crucible, and heat treating it in a 1:9 oxygen-nitrogen mixed atmosphere at a temperature of 1000° C. for 30 minutes to obtain a second powder;
[0096] Step (C), mixing the second powder obtained in step (B) with HF acid having a concentration of 1 mol / L in a mass ratio of 1:5, and mechanically stirring at 60° C. for 30 minutes to obtain a mixture;
[0097] Step (D), filtering the mixture obtained in step (C) through a polytetrafluoroethylene filter membrane with a pore size of 200 nm, and drying the solid matter on the filter membrane at 100° C. for 1 h to obtain a third powder;
[0098] Step (E), the third powder obtained in step (D) is treated four times in sequence according to step (B), step (C) and step (D) to obtain a fourth powder;
[0099] Step (F), washing the fourth powder obtained in step (E) with deionized water until fluoride ions are no longer detected in the washing wastewater, to obtain a fifth powder;
[0100] Step (G), drying the fifth powder obtained in step (F) at 100° C. for 1 hour, and finally obtaining a material.
[0101] Using a scanning electron microscope, the appearance of the phosphor is approximately spherical. The luminescence performance of the sample obtained in Example 2 was tested using a fluorescence spectrometer. The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Example 2 is located at 514 nm. The median particle size of the obtained sample was measured using a laser particle size analyzer, and the results showed that the D50 median particle size of the obtained sample was 0.82 μm. Obviously, this median particle size value can meet the packaging application for Mini LED backlight sources. Compared with Comparative Example 1, this value has dropped significantly, which is obviously because silicon dioxide is generated on the surface of the particles (heat treatment in an oxidizing atmosphere), but after HF acid treatment, the silicon dioxide on the surface of the phosphor particles is corroded, resulting in a significant reduction in the final median particle size of the particles; and compared with Comparative Example 4, after 5 oxidation / HF calculation washings, the median particle size value of the phosphor particles can meet the requirements of the packaging application of Mini LED backlight sources. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since no destructive ball milling process was used, the result was 49.6% under 450 nm blue light excitation. The specific data is shown in Table 1.
[0102] That is, the material obtained in Example 2 is a green nitride phosphor and can meet the packaging requirements of Mini LED backlight sources.
[0103] Example 3
[0104] Follow the steps below to make it:
[0105] Step (A), Sr3N2, EuN, Li3N and Si3N4 are mixed in a ratio of 0.97:0.03:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder, and then the mixed powder is placed in a crucible, and sintered at 1600° C. in an ammonia atmosphere of 2 MPa for 6 hours to obtain a first powder;
[0106] Step (B), grinding the first powder obtained in step (A) and placing it in a crucible, and heat treating it in a 1:9 oxygen-nitrogen mixed atmosphere at a temperature of 1000° C. for 30 minutes to obtain a second powder;
[0107] Step (C), mixing the second powder obtained in step (B) with HF acid having a concentration of 1 mol / L in a mass ratio of 1:5, and mechanically stirring at 60° C. for 30 minutes to obtain a mixture;
[0108] Step (D), filtering the mixture obtained in step (C) through a polytetrafluoroethylene filter membrane with a pore size of 200 nm, and drying the solid matter on the filter membrane at 100° C. for 1 h to obtain a third powder;
[0109] Step (E), the third powder obtained in step (D) is treated four times in sequence according to step (B), step (C) and step (D) to obtain a fourth powder;
[0110] Step (F), washing the fourth powder obtained in step (E) with deionized water until fluoride ions are no longer detected in the washing wastewater, to obtain a fifth powder;
[0111] Step (G), drying the fifth powder obtained in step (F) at 100° C. for 1 hour, and finally obtaining a material.
[0112] Using a scanning electron microscope, the appearance of the phosphor is approximately spherical. The luminescence performance of the sample obtained in Example 3 was tested using a fluorescence spectrometer. The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Example 3 is located at 517 nm. The median particle size of the obtained sample was measured using a laser particle size analyzer. The results showed that the D50 median particle size of the obtained sample was 0.75 μm. Obviously, this median particle size value can meet the packaging application for Mini LED backlight sources. Compared with Comparative Example 1, this value has dropped significantly, which is obviously because silicon dioxide is generated on the surface of the particles (heat treatment in an oxidizing atmosphere), but after HF acid treatment, the silicon dioxide on the surface of the phosphor particles is corroded, resulting in a significant reduction in the final median particle size of the particles; and compared with Comparative Example 4, after 5 oxidation / HF calculation washings, the median particle size value of the phosphor particles can meet the requirements of the packaging application of Mini LED backlight sources. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since no destructive ball milling process was used, the result was 52.4% under 450 nm blue light excitation. See Table 1 for specific data.
[0113] That is, the material obtained in Example 3 is a green nitride phosphor and can meet the packaging requirements of Mini LED backlight sources.
[0114] Example 4
[0115] Follow the steps below to make it:
[0116] Step (A), Sr3N2, EuN, Li3N and Si3N4 are mixed in a ratio of 0.96:0.04:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder, and then the mixed powder is placed in a crucible, and sintered at 1600° C. in an ammonia atmosphere of 2 MPa for 6 hours to obtain a first powder;
[0117] Step (B), grinding the first powder obtained in step (A) and placing it in a crucible, and heat treating it in a 1:9 oxygen-nitrogen mixed atmosphere at a temperature of 1000° C. for 30 minutes to obtain a second powder;
[0118] Step (C), mixing the second powder obtained in step (B) with HF acid having a concentration of 1 mol / L in a mass ratio of 1:5, and mechanically stirring at 60° C. for 30 minutes to obtain a mixture;
[0119] Step (D), filtering the mixture obtained in step (C) through a polytetrafluoroethylene filter membrane with a pore size of 200 nm, and drying the solid matter on the filter membrane at 100° C. for 1 h to obtain a third powder;
[0120] Step (E), the third powder obtained in step (D) is treated four times in sequence according to step (B), step (C) and step (D) to obtain a fourth powder;
[0121] Step (F), washing the fourth powder obtained in step (E) with deionized water until fluoride ions are no longer detected in the washing wastewater, to obtain a fifth powder;
[0122] Step (G), drying the fifth powder obtained in step (F) at 100° C. for 1 hour, and finally obtaining a material.
[0123] Using a scanning electron microscope, the appearance of the phosphor is approximately spherical. The luminescence performance of the sample obtained in Example 4 was tested using a fluorescence spectrometer. The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Example 4 is located at 520 nm. The median particle size of the obtained sample was measured using a laser particle size analyzer, and the results showed that the D50 median particle size of the obtained sample was 0.62 μm. Obviously, this median particle size value can meet the packaging application for Mini LED backlight sources. Compared with Comparative Example 1, this value has dropped significantly, which is obviously because silicon dioxide is generated on the surface of the particles (heat treatment in an oxidizing atmosphere), but after HF acid treatment, the silicon dioxide on the surface of the phosphor particles is corroded, resulting in a significant reduction in the final median particle size of the particles; and compared with Comparative Example 4, after 5 oxidation / HF calculation washings, the median particle size value of the phosphor particles can meet the requirements of the packaging application of Mini LED backlight sources. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since no destructive ball milling process was used, the result was 56.8% under 450 nm blue light excitation. See Table 1 for specific data.
[0124] That is, the material obtained in Example 4 is a green nitride phosphor and can meet the packaging requirements of Mini LED backlight sources.
[0125] Example 5
[0126] Follow the steps below to make it:
[0127] Step (A), Sr3N2, EuN, Li3N and Si3N4 are mixed in a ratio of 0.95:0.05:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder, and then the mixed powder is placed in a crucible, and sintered at 1600° C. in an ammonia atmosphere of 2 MPa for 6 hours to obtain a first powder;
[0128] Step (B), grinding the first powder obtained in step (A) and placing it in a crucible, and heat treating it in a 1:9 oxygen-nitrogen mixed atmosphere at a temperature of 1000° C. for 30 minutes to obtain a second powder;
[0129] Step (C), mixing the second powder obtained in step (B) with HF acid having a concentration of 1 mol / L in a mass ratio of 1:5, and mechanically stirring at 60° C. for 30 minutes to obtain a mixture;
[0130] Step (D), filtering the mixture obtained in step (C) through a polytetrafluoroethylene filter membrane with a pore size of 200 nm, and drying the solid matter on the filter membrane at 100° C. for 1 h to obtain a third powder;
[0131] Step (E), the third powder obtained in step (D) is treated four times in sequence according to step (B), step (C) and step (D) to obtain a fourth powder;
[0132] Step (F), washing the fourth powder obtained in step (E) with deionized water until fluoride ions are no longer detected in the washing wastewater, to obtain a fifth powder;
[0133] Step (G), drying the fifth powder obtained in step (F) at 100° C. for 1 hour, and finally obtaining a material.
[0134] Using a scanning electron microscope, the appearance of the phosphor is approximately spherical. The luminescence performance of the sample obtained in Example 5 was tested using a fluorescence spectrometer. The test data is shown in Figure 3 . The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Example 5 is located at 523 nm. The median particle size of the obtained sample was measured using a laser particle size analyzer. The results showed that the D50 median particle size of the obtained sample was 0.61 μm. Obviously, this median particle size value can meet the packaging application for Mini LED backlight sources. Compared with Comparative Example 1, this value has dropped significantly, which is obviously because silicon dioxide is generated on the surface of the particles (heat treatment under oxidizing atmosphere), but after HF acid treatment, the silicon dioxide on the surface of the phosphor particles is corroded, resulting in a significant decrease in the final median particle size of the particles; and compared with Comparative Example 4, after 5 oxidation / HF calculation washings, the median particle size value of the phosphor particles can meet the requirements of the packaging application of Mini LED backlight sources. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since no destructive ball milling process was used, the result was 59.8% under 450 nm blue light excitation. See Table 1 for specific data.
[0135] That is, the material obtained in Example 5 is a green nitride phosphor and can meet the packaging requirements of Mini LED backlight sources.
[0136] Example 6
[0137] Follow the steps below to make it:
[0138] Step (A), Sr3N2, EuN, Li3N and Si3N4 are mixed in a ratio of 0.94:0.06:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder, and then the mixed powder is placed in a crucible, and sintered at 1600° C. in an ammonia atmosphere of 2 MPa for 6 hours to obtain a first powder;
[0139] Step (B), grinding the first powder obtained in step (A) and placing it in a crucible, and heat treating it in a 1:9 oxygen-nitrogen mixed atmosphere at a temperature of 1000° C. for 30 minutes to obtain a second powder;
[0140] Step (C), mixing the second powder obtained in step (B) with HF acid having a concentration of 1 mol / L in a mass ratio of 1:5, and mechanically stirring at 60° C. for 30 minutes to obtain a mixture;
[0141] Step (D), filtering the mixture obtained in step (C) through a polytetrafluoroethylene filter membrane with a pore size of 200 nm, and drying the solid matter on the filter membrane at 100° C. for 1 h to obtain a third powder;
[0142] Step (E), the third powder obtained in step (D) is treated four times in sequence according to step (B), step (C) and step (D) to obtain a fourth powder;
[0143] Step (F), washing the fourth powder obtained in step (E) with deionized water until fluoride ions are no longer detected in the washing wastewater, to obtain a fifth powder;
[0144] Step (G), drying the fifth powder obtained in step (F) at 100° C. for 1 hour, and finally obtaining a material.
[0145] Using a scanning electron microscope, the appearance of the phosphor is approximately spherical. The luminescence performance of the sample obtained in Example 6 was tested using a fluorescence spectrometer. The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Example 6 is located at 527 nm. The median particle size of the obtained sample was measured using a laser particle size analyzer, and the results showed that the D50 median particle size of the obtained sample was 0.55 μm. Obviously, this median particle size value can meet the packaging application for Mini LED backlight sources. Compared with Comparative Example 1, this value has dropped significantly, which is obviously because silicon dioxide is generated on the surface of the particles (heat treatment in an oxidizing atmosphere), but after HF acid treatment, the silicon dioxide on the surface of the phosphor particles is corroded, resulting in a significant reduction in the final median particle size of the particles; and compared with Comparative Example 4, after 5 oxidation / HF calculation washings, the median particle size value of the phosphor particles can meet the requirements of the packaging application of Mini LED backlight sources. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since no destructive ball milling process was used, the result was 51.7% under 450 nm blue light excitation. The specific data is shown in Table 1.
[0146] That is, the material obtained in Example 6 is a green nitride phosphor and can meet the packaging requirements of Mini LED backlight sources.
[0147] Example 7
[0148] Follow the steps below to make it:
[0149] Step (A), Sr3N2, EuN, Li3N and Si3N4 are mixed in a ratio of 0.93:0.07:1:3 in a nitrogen atmosphere in a glove box to obtain a mixed powder, and then the mixed powder is placed in a crucible, and sintered at 1600° C. in an ammonia atmosphere of 2 MPa for 6 hours to obtain a first powder;
[0150] Step (B), grinding the first powder obtained in step (A) and placing it in a crucible, and heat treating it in a 1:9 oxygen-nitrogen mixed atmosphere at a temperature of 1000° C. for 30 minutes to obtain a second powder;
[0151] Step (C), mixing the second powder obtained in step (B) with HF acid having a concentration of 1 mol / L in a mass ratio of 1:5, and mechanically stirring at 60° C. for 30 minutes to obtain a mixture;
[0152] Step (D), filtering the mixture obtained in step (C) through a polytetrafluoroethylene filter membrane with a pore size of 200 nm, and drying the solid matter on the filter membrane at 100° C. for 1 h to obtain a third powder;
[0153] Step (E), the third powder obtained in step (D) is treated four times in sequence according to step (B), step (C) and step (D) to obtain a fourth powder;
[0154] Step (F), washing the fourth powder obtained in step (E) with deionized water until fluoride ions are no longer detected in the washing wastewater, to obtain a fifth powder;
[0155] Step (G), drying the fifth powder obtained in step (F) at 100° C. for 1 hour, and finally obtaining a material.
[0156] Using a scanning electron microscope, the appearance of the phosphor is approximately spherical. The luminescence performance of the sample obtained in Example 7 was tested using a fluorescence spectrometer. The results show that under 450 nm blue light excitation, the main peak of the emission spectrum of the material obtained in Example 7 is located at 530 nm. The median particle size of the obtained sample was measured using a laser particle size analyzer. The results showed that the D50 median particle size of the obtained sample was 0.51 μm. Obviously, this median particle size value can meet the packaging application for Mini LED backlight sources. Compared with Comparative Example 1, this value has dropped significantly, which is obviously because silicon dioxide is generated on the surface of the particles (heat treatment in an oxidizing atmosphere), but after HF acid treatment, the silicon dioxide on the surface of the phosphor particles is corroded, resulting in a significant reduction in the final median particle size of the particles; and compared with Comparative Example 4, after 5 oxidation / HF calculation washings, the median particle size value of the phosphor particles can meet the requirements of the packaging application of Mini LED backlight sources. The quantum efficiency of the sample was tested using a quantum efficiency tester. Since no destructive ball milling process was used, the result was 50.3% under 450 nm blue light excitation. The specific data is shown in Table 1.
[0157] That is, the material obtained in Example 7 is a green nitride phosphor and can meet the packaging requirements of Mini LED backlight sources.
[0158] Example 8
[0159] The small-particle spherical green nitride phosphor obtained in Example 5 is packaged with a Mini LED having an emission wavelength of 450 nm and a plane size of 200 μm×200 μm. The specific packaging process is: the small-particle spherical green nitride phosphor obtained in Example 5 is mixed with epoxy resin in a mass ratio of 1:2.11, and then coated on the surface of the Mini LED having an emission wavelength of 450 nm and a plane size of 200 μm×200 μm, and then cured at 150°C for 30 minutes to obtain a Mini LED device. Figure 4 A physical picture of the device obtained in Example 8 is given.
[0160] Table 1 Luminescence performance data of small-size spherical green nitride phosphor
[0161]
[0162] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A small-particle spherical green nitride phosphor for MiniLED backlight applications, characterized by: The small-particle spherical green nitride phosphor is made of Sr 1-x Eu x The general chemical formula of LiSi3N5 is represented, wherein 0.01≤x≤0.07; the main peak of the emission spectrum of the small-particle spherical green nitride phosphor under 450 nm blue light excitation is 510 nm to 530 nm; the D50 median particle size of the small-particle spherical green nitride phosphor is 0.5 μm to 1 μm.
2. The small-diameter spherical green nitride phosphor for MiniLED backlight application according to claim 1, characterized in that: The small-particle spherical green nitride phosphor can absorb violet light and blue light; under the excitation of 450 nm blue light, the quantum efficiency of the small-particle spherical green nitride phosphor is 40% to 60%.
3. A method for preparing a small-diameter spherical green nitride phosphor for MiniLED backlight application according to any one of claims 1 to 2, characterized in that: The steps include: 1) Sr3N2, EuN, Li3N and Si3N4 are mixed evenly under a protective atmosphere, and then sintered under an ammonia atmosphere to obtain a first powder; 2) grinding the first powder and heat treating it in an oxidizing atmosphere to obtain a second powder; 3) mixing the second powder with HF acid, heating and stirring to obtain a mixture; 4) filtering the mixture in step 3) using a filter membrane, and drying the obtained solid to obtain a third powder; 5) Repeating step 2), step 3) and step 4) for 4 times on the third powder to obtain a fourth powder; 6) washing the fourth powder with deionized water to obtain a fifth powder; 7) Drying the fifth powder to obtain the small-size spherical green nitride phosphor.
4. The preparation method according to claim 3, characterized in that: In step 1), the molar ratio of Sr to Eu to Li to Si in the Sr3N2, EuN, Li3N and Si3N4 is (1-x):x:1:
3.
5. The preparation method according to claim 3, characterized in that: In step 1), the pressure of the ammonia atmosphere is 1.5 MPa to 2 MPa, the sintering temperature is 1550° C. to 1600° C., and the sintering time is 6 h to 10 h.
6. The preparation method according to claim 3, characterized in that: In step 2), the heat treatment temperature is 1000° C. to 1100° C., and the heat treatment time is 25 min to 30 min.
7. The preparation method according to claim 3, characterized in that: In step 6), washing is performed until no fluoride ions are detected.
8. A Mini LED backlight source, characterized in that: include: Mini LED and wavelength conversion material, the wavelength conversion material comprising the small-particle spherical green nitride phosphor as described in any one of claims 1 to 2 or the small-particle spherical green nitride phosphor obtained by the preparation method of any one of claims 3 to 7.
9. A Mini LED backlight source according to claim 8, characterized in that: The emission wavelength range of the Mini LED is 380 nm to 480 nm, and the plane size is 200 μm×200 μm.
Citation Information
Patent Citations
Nitride fluorescent powder with small particle size and high quantum efficiency, preparation method and application thereof, luminescent device and display device
CN112745835A
Preparation method of fluorescent powder with small particle size
CN112980435A
Small-particle-size red fluorescent powder and preparation method thereof
CN114806576A
Small-particle-size nitride narrow-band green fluorescent powder and preparation method thereof
CN115093851A
Light-emitting film of high-uniformity mini-LED backlight source and preparation method of light-emitting film
CN117106212A